GPR55 and GPR119 Receptors Contribute to the Processing of Neuropathic Pain in Rats - Ángel Zúñiga-Romero; Quetzali Rivera-Plata; Jesús Arrieta; Francisco Javier Flores-Murrieta; Juan Rodríguez-Silverio; Juan Gerardo Reyes-García; Juan Carlos Huerta-Cruz; Gustavo Ramírez-Martínez; Héctor Isaac Rocha-González (MDPI AG, 2022)
Orphan G-protein-coupled receptors (GPCR) comprise a large number of receptors which are widely distributed in the nervous system and represent an opportunity to identify new molecular targets in pain medicine. GPR55 and GPR119 are two orphan GPCR receptors whose physiological function is unclear. The aim was to explore the participation of spinal GPR55 and GPR119 in the processing of neuropathic pain in rats. Mechanical allodynia was evaluated using von Frey filaments. Protein localization and modulation were measured by immunohistochemistry and western blotting, respectively. Intrathecal administration of CID16020046 (selective GPR55 antagonist) or AS1269574 (selective GPR119 agonist) produced a dose-dependent antiallodynic effect, whereas O1062 (GPR55 agonist) and G-protein antagonist peptide dose-dependently prevented the antiallodynic effect of CID16020046 and AS1269574, respectively. Both GPR55 and GPR119 receptors were expressed in spinal cord, dorsal root ganglia and sciatic nerve, but only GPR119 was downregulated after 14 days of spinal nerve ligation. Data suggest that GPR55 and GPR119 participate in the processing of neuropathic pain and could be useful targets to manage neuropathic pain disorders.